2011
DOI: 10.1007/s00894-011-1161-x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on models of lysine-arginine cross-links derived from α-oxoaldehydes: a new mechanism for glucosepane formation

Abstract: Availability and high reactivity of α-oxoaldehydes have been approved by experimental techniques not only in vivo systems but also in foodstuffs. In this article we re-examine the mechanism of glucosepane formation by using computational model chemistry. Density functional theory has been applied to propose a new mechanism for glucosepane formation through reaction of α-oxoaldehydes with methyl amine (MA) and methyl guanidine (MGU) models of lysine and arginine residues respectively. This non enzymatic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…3, implies a non-oxidative reaction initiated by FL reacting with an arginine residue via a so-called dideoxyglucosone intermediate. Very recently, an alternative, highly complex mechanism initiated by methylglyoxal, and followed by glyceraldehyde addition, was proposed based on computational calculations 28 . However, the role of this mechanism for GSPNE formation in diabetes is questionable since we were unable to find mass spectrometric evidence for in vivo formation of triosidines (unpublished data), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…3, implies a non-oxidative reaction initiated by FL reacting with an arginine residue via a so-called dideoxyglucosone intermediate. Very recently, an alternative, highly complex mechanism initiated by methylglyoxal, and followed by glyceraldehyde addition, was proposed based on computational calculations 28 . However, the role of this mechanism for GSPNE formation in diabetes is questionable since we were unable to find mass spectrometric evidence for in vivo formation of triosidines (unpublished data), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this form of carbonyl stress would proceed anaerobically in diabetes and be insensitive to antioxidants! Interestingly, Nasiri et al found, based on theoretical considerations, that glucosepane might possibly originate from a combination of methylglyoxal and glyceraldehyde [15]. In unpublished preliminary studies, we have found that glyceraldehyde, but not methylglyoxal, generates glucosepane-like m/z species in our LC/MS chromatogram.…”
Section: Glucosepane: Chemistry and Mechanism Of Formationmentioning
confidence: 48%
“…28,61,[64][65][66][67] The reaction between these precursors and amino groups of proteins could happen either oxidatively or non-oxidatively, giving rise to different types of AGEs. The group of intermediate compounds produced during Amadori rearrangements, including the reactive carbonyl species (glyoxal, methylglyoxal and 3-deoxyglucosone) have been proposed to be the immediate precursors of AGEs.…”
Section: Advanced Glycation Endproducts (Ages)mentioning
confidence: 99%
“…The group of intermediate compounds produced during the Amadori rearrangements, including the reactive carbonyl species (glyoxal, methylglyoxal and 3-deoxyglucosone), have been proposed to be the immediate precursors of AGEs. 28,61,[64][65][66][67] The reaction between these precursors and the amino groups of proteins could happen either oxidatively or non-oxidatively, giving rise to different types of AGEs. 68 Carboxymethyllysine (CML) and pentosidine are two of the best Fig.…”
Section: Advanced Glycation End Products (Ages)mentioning
confidence: 99%